Leveraging Protected Species Observer (PSO) data for conservation in offshore wind energy development - Craig Reiser; Melinda Conners; Mari A. Smultea (npj Ocean Sustainability)
The rapidly expanding offshore wind energy industry presents an unprecedented opportunity to collect valuable data on protected marine species, particularly the endangered North Atlantic right whale (Eubalaena glacialis), through required Protected Species Observer (PSO) programs. PSO data, gathered during industry activities by trained biologists in often remote and challenging offshore environments, can fill critical knowledge gaps regarding species distribution, occurrence, and interactions with development, informing conservation and management strategies. While challenges remain regarding data accessibility, standardization, and integration, ongoing initiatives by agencies like the US National Marine Fisheries Service and Bureau of Ocean Energy Management coupled with existing data-sharing efforts and open-source platforms, offer pathways to maximize the value of PSO data. Realizing this potential requires collaborative partnerships between industry, agencies, researchers, and other stakeholders to establish centralized, publicly accessible databases with standardized protocols and adequate funding for data management. Successfully leveraging PSO data will significantly enhance our understanding of marine species and contribute to their conservation in the face of increasing offshore development.